Prevalence of risk factors for non-communicable diseases in Bangladesh: Results from STEPS survey 2010 - Zaman, MohammadMostafa; Rahman, Md. Mujibur; Rahman, Md. Ridwanur; Bhuiyan, MahfuzurRahman; Karim, Md. Nazmul; Chowdhury, Md. AbdulJalil (Indian journal of public health, 2016)
Nationally representative data on noncommunicable disease (NCD) risk factors are lacking in Bangladesh. This study was done to determine the prevalence of common risk factors for major NCDs among men and women of rural and urban areas of Bangladesh. This survey was done with 9,275 individuals aged 25 years or older randomly drawn from all over the country. Information on diet, physical activity, tobacco and alcohol, and treatment history for hypertension and diabetes were collected. Height, weight, waist circumference, and blood pressure (BP) were measured. There were 4,312 men and 4,963 women with the mean age of 42 years (standard deviation 13 years). Half of them (54%) used tobacco in some form, <1% consumed alcohol within the past 30 days, 92% did not consume adequate fruit and vegetables (five servings or more), and 35% had low physical activity level [<600 metabolic equivalent (MET) min per week]. Documented diabetes was found in 4% of the participants. Seventeen percent were overweight [body mass index (BMI) ≥25 kg/m 2 and 21% had abdominal obesity (men ≥94, women ≥80 cm). Overall, 21% people had hypertension (blood pressure ≥140/90 mmHg or medication). Physical inactivity, alcohol intake, hypertension, obesity, and diabetes were more prevalent in urban areas, as opposed to tobacco. Tobacco intake showed a decreasing gradient, but hypertension, obesity, diabetes, and low physical activity showed an increasing gradient across the wealth quartiles. Risk factors are widely prevalent in Bangladeshi people across sexes and across both rural and urban areas of residences. NCD prevention through risk factor control, and early detection and treatment of hypertension and diabetes are warranted.